Mountain farmers' intangible values foster agroecological landscapes: case studies from Sierra Santa Victoria in northwest Argentina and the Ladin Dolomites, northern Italy - Steinhäuser, Cornelia (Agroecology and sustainable food systems, 2020)
Agroecological landscapes, which promote critical features such as agrobiodiversity, represent valuable global commons. These landscapes are products of ways of life, local knowledge, and rural practices. Recent studies agree on the need to better understand such rooted social-ecological systems by more deeply exploring their human-environment relationships. To address this, we investigated agroecological landscapes in two communities, one in the Andean highlands of northwest Argentina, the other in the Dolomites in northern Italy. This research applies discourse-ethnographic methods to explore how the communities build institutions to protect their culture, how they manage change, and how the environment is perceived and used. Based on the results, we identified several dimensions of farmers' intangible values, their understanding of well-being, and how they contribute to the genesis of landscapes (maize terraces, alpine pastures). This work shows that many interviewees did not perceive nature merely as a resource or service for humans, as suggested by the widely held discourse of agricultural industrialization, and that alternative relationships to nature are possible and do exist in practice. Further, this work raises relevant issues for how to imagine the transition to agricultural systems that do not define well-being only from the perspective of materiality and of humans.